GENETIC VARIABILITY, ASSOCIATION AND DIVERSITY STUDIES IN BREAD WHEAT (TRITICUM AESTIVUM L.) - BINOD KUMAR; CHANDRA MOHAN SINGH; KUNDAN KUMAR JAISWAL (The Bioscan, 2013)
Thirty wheat genotypes significant genotypic differences were observed for all the traits studied indicated the considerable amount of variation among genotypes for each character. The estimates of GCV and PCV were moderate for biological yield per plant, number of effective tillers per plant. High heritability estimates were recorded for all the traits and also indicated high genetic advance (except days to 50% flowering and days to maturity). Grain yield per plant showed highly significant positive correlation with 1000 seed weight, plant height and number of effective tillers per plant, spike length and 1000 seed weight highly significant positive correlation with grains per spike. Path coefficient analysis revealed that 1000 seed weight and plant height had the highest direct effect on grain yield per plant and each must be given preference in selection along superior wheat genotypes. On the basis of maximum divergence, inter-mating of K816 and HUW-533 mono-cluster genotypes from cluster VI and VII showing maximum inter-cluster distance between them followed by monocluster genotype K816 from cluster VI with 3 genotypes from cluster II exihibiting high degree of genetic diversity may be utilized through inter-varietal hybridization programme. Noteworthy is that cluster II and VI exhibited high cluster means for seed yield per plant, grains per spike and spike length; cluster VI and VII for tillers per plant, seed yield per plant and test weight and it also exhibited high heritability coupled with high genetic advance as percent of mean, might be utilized in hybridization- selection breeding for wheat genotypes.